Reinventing Government as Design Innovation on Palopo City Regional Government - Mustaming, Mustaming; Ulfa, Ulfa; Armin, Rizka Amelia (Universitas Teuku Umar, 2024)
Designing bureaucratic reforms is not only about simplifying the bureaucratic structure, but the main thing is to change the mindset and bureaucratic culture patterns in governance. Therefore, reinventing Government is implemented into the government system. This study aims to analyze reinventing Government in the innovation of the Palopo City regional government and the strategy for developing regional innovation. This type of qualitative descriptive research is used to analyze and examine Reinventing Government in the Innovation of Regional Government Bureaucracy. Data collection in the fields through observation, interviews with innovation innovators, community users of innovation services, those responsible for the Palopo City Regional Innovation Index, and focused group discussions with public policy experts, and documentation, the data obtained are then analyzed by data reduction, displaying data, concluding conclusion, and verification. The study results indicate that regional innovations made in Palopo City are based on the principles of Reinventing Government, such as catalytic Government, mission-driven Government, results-oriented Government, decentralized Government, and anticipatory Government. However, the principles of reinventing governance, such as customer-oriented Government, community-owned and market-oriented Government, and entrepreneurial Government, have not been wholly implemented because the regional innovations created are individual, so it is hopefully that collaborative innovation can be applied to develop new ideas and creative solutions in regional Government.